Coordination of innate immune responses by connexins - Wu, Qirou; Zhao, Tiejun; Xu, Pinglong (Frontiers in Immunology, 2025)
Innate immunity comprises intricate cellular and tissue responses critical for host defense and tissue homeostasis. Intercellular communication is central to these responses and significantly influences infection, inflammatory disorders, and cancer. Connexins form hemichannels, gap junctions, and connexosomes to mediate signaling molecule transfer, including nucleotide derivatives, ions, antigens, and mitochondria, which occur between adjacent cells or between cells and their microenvironments. By modulating intercellular communication, connexins regulate various immune cell functions and contribute significantly to the coordination of innate immunity. This review summarizes recent insights into connexin-mediated innate immune networks and their implications in pathological contexts such as viral infections, inflammation, and tumorigenesis. Additionally, we discuss targeting connexins as an emerging pharmacological strategy for clinical intervention.